Adjunctive zonisamide therapy in the long‐term treatment of children with partial epilepsy: Results of an open‐label extension study of a phase III, randomized, double‐blind, placebo‐controlled trial. Issue 4 (22nd February 2014) - Guerrini, Renzo; Rosati, Anna; Bradshaw, Kate; Giorgi, Luigi
Summary Objective To investigate the safety/tolerability and efficacy of long‐term adjunctive zonisamide and its impact on growth and development in children (6–18 years) with partial epilepsy. Methods Open‐label extension of a phase III, placebo‐controlled trial. Started with double‐blind transition period (2–11 weeks), during which patients on zonisamide continued at the same dose and those on placebo switched to zonisamide 1 mg/kg/day, up‐titrated to 8 mg/kg/day (maximum 500 mg/day). During the subsequent open‐label period (45–57 weeks), zonisamide dosing could be adjusted according to tolerability/response. Safety assessments included treatment‐emergent adverse events (TEAEs), clinical laboratory parameters, and vital signs. Efficacy assessments included responder rate (primary assessment) and seizure freedom rate during the open‐label period. Growth and development assessments comprised Tanner stages, hand x‐rays, Child Behavior Checklist (CBCL 6/18), School Performance questionnaire, Physician and Parent/Guardian Global Impression of Change, and Controlled Oral Word Association Test (COWAT). Results One hundred forty‐four children entered the study; 99 (68.8%) of 144 children completed it, and 108 (75.0%) of 144 received zonisamide for ≥1 year. TEAEs occurred in 39 (27.1%) of 144 patients. There were low incidences of serious TEAEs (2.1%) and TEAEs leading to discontinuation (2.8%). Bicarbonate level decreases >3.5 mm occurred in 64 patients (44.4%), and 24 patients (16.7%) had a weight decrease of ≥10% from baseline. During the open‐label period, 81 (56.3%) of 144 patients were responders and 16 (11.1%) of 144 achieved seizure freedom. Tanner staging and skeletal development were as expected for the study population. Changes were minimal for CBCL 6/18 and School Performance scores. Most patients were "much improved"/"very much improved" on Physician (73.8%) and Parent/Guardian (75.4%) Global Impressions of Change. Median changes in COWAT Category and Letter Fluency scores were 2.0 and 0.5, respectively. Significance Adjunctive zonisamide was well tolerated and efficacious over a period of at least 1 year in children with partial epilepsy, with no unexpected safety concerns and no consistent detrimental effects on growth and development. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.